Aero-acoustics prediction of a vertical axis wind turbine using Large Eddy Simulation and acoustic analogy. (August 2015) - Ghasemian, Masoud; Nejat, Amir
Abstract: Operating wind turbines generate tonal and broadband noises affecting the living environment adversely; especially small wind turbines located in the vicinity of human living places. Therefore, it is important to determine the level of noise pollution of such type of wind turbine installation. The current study carries out numerical prediction for aerodynamic noise radiated from an H-Darrieus Vertical Axis Wind Turbine. Incompressible LES (Large Eddy Simulation) is conducted to obtain the instantaneous turbulent flow field. The noise predictions are performed by the Ffowcs Williams and Hawkings (FW–H) acoustic analogy formulation. Simulations are performed for five different tip-speed ratios. First, the mean torque coefficient is compared with the experimental data, and good agreement is observed. Then, the research focuses on the broadband noises of the turbulent boundary layers and the tonal noises due to blade passing frequency. The contribution of the thickness, loading and quadrupole noises are investigated, separately. The results indicate a direct relation between the strength of the radiated noise and the rotational speed. Furthermore, the effect of receiver distance on the OASPL (Overall Sound Pressure Level) is investigated. It is concluded that the OASPL varies with a logarithmic trend with the receiver distance as it was expected. Highlights: Large Eddy Simulation has been used to predict the turbulent flow field. The Ffowcs Williams and Hawkings method was employed to predict radiated noise. There is a direct relation between the radiated noise and the tip speed ratio. The quadrupole noises have negligible effect on the tonal noises.